Space Equations - Jessii, Prince (Annals of Mathematics and Physics, 2019)
Trying to observe the reason behind the differences in the nature of space that exists on earth and on the outer space led to the path were space and gravity meets. This paper presents a theory which comprises of an already existing effect that has helped to determine the following: • Space constant. • The Relationship between Space and Gravity. • Formulation of Space Equations. • Verification of the value of acceleration due to gravity, mass, radius of most planetary bodies. • The Fate of the existence of parallel universes.